Alterations of Serum Bile Acid Profile in Patients with Crohn’s Disease - Rui Sun; Jingjing Jiang; Ling Yang; Lu Chen; Hong Chen (Gastroenterology Research and Practice)
Background. Bile acid (BA) metabolism may be influenced by gut dysbiosis and alterations of intestinal epithelium in patients with Crohn’s disease (CD). Here, we aimed at investigating the alterations of serum BA profile in CD patients and analyzing the correlation between BAs and CD disease activity. Methods. A total of 62 CD patients (29 active and 33 remission) and 33 healthy volunteers (HVs) were enrolled in this retrospective study. Serum BA profiles were measured by liquid chromatography-tandem mass spectrometry. Results. Levels of primary BAs components, including cholic acid (CA) and chenodeoxycholic acid (CDCA), showed no significant difference when compared with HVs. Secondary BAs (SBA) were significantly decreased in CD patients compared with HVs. Importantly, the deoxycholic acid (DCA) and glycodeoxycholic acid (GDCA) levels were significantly lower in CD active than in CD remission patients. The DCA/(DCA + CA) ratio was also decreased in CD active patients than in CD remission patients while the LCA/(LCA + CDCA) ratio showed no difference between them. Principal component analysis also indicated a clear separation among the three groups, with a total variance of 93.43%. The correlation analysis showed that the SBA, DCA, GDCA levels, and DCA/(DCA + CA) ratio had an inverse relationship with Crohn’s Disease Activity Index. Conclusion. The BA profile exhibits significant alterations in CD patients. The SBA, DCA, GDCA levels, and DCA/(DCA + CA) ratio were significantly decreased in CD active patients. The DCA/(DCA + CA) ratio had an inverse correlation with CD disease activity.